Plant Proteomic Research 2.0 - Komatsu, Setsuko (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Advancements in high-throughput "Omics" techniques have revolutionized plant molecular biology research. Proteomics offers one of the best options for the functional analysis of translated regions of the genome, generating a wealth of detailed information regarding the intrinsic mechanisms of plant stress responses. Various proteomic approaches are being exploited extensively for elucidating master regulator proteins which play key roles in stress perception and signaling, and these approaches largely involve gel-based and gel-free techniques, including both label-based and label-free protein quantification. Furthermore, post-translational modifications, subcellular localization, and protein-protein interactions provide deeper insight into protein molecular function. Their diverse applications contribute to the revelation of new insights into plant molecular responses to various biotic and abiotic stressors.